ChemInform Abstract: A Convenient Synthesis of γ‐Amino‐ynamides via Additions of Lithiated Ynamides to Aryl Imines; Observation of an Aza‐Meyer—Schuster Rearrangement. Issue 44 (14th October 2013) - Tang, Yu; et al., et al.
Abstract The synthesis of γ‐amino‐ynamides via nucleophilic addition of lithiated ynamides to aryl amines is developed and the use of the products in subsequent derivatization reactions is demonstrated.